Implementação das plataformas digitais no processo de alfabetização das escolas do estado de SãoPaulo: desafios à formação docente e à autonomia pedagógica - Piccirilli, Giovanna Maria Recco (Universidade Federal de São Carlos, 2026)
This dissertation analyzes the incorporation of digital platforms in the literacy process in the early years of Elementary School in the São Paulo state network, focusing on the implications of these technologies for teaching work, teacher training and public policies for digital education. Anchored in the qualitative approach, the research articulates literature review, analysis of normative documents and production of empirical data through interviews with literacy teachers and with the person responsible for the Center for Educational and Technological Information. The theoretical framework mobilizes contributions from Dermeval Saviani's (2021) Historical-Critical Pedagogy and Maurice Tardif's (2014) sociology of teaching knowledge, allowing us to understand the platformization of teaching as a contradictory process, marked by tensions between standardization, control, and pedagogical mediation. The results show that the implementation of the platforms occurs in a predominantly verticalized way, with teacher training centered on the instrumental use of the tools, which stresses professional autonomy and intensifies the teaching work, in addition to evidencing inequalities in the conditions of access and use of technologies. It is concluded that the use of digital platforms in literacy demands public policies that articulate infrastructure, critical teacher training and valorization of pedagogical work, recognizing the teacher as an intentional mediator of the educational process, contributing to studies in the area of language and teacher training.
Implementation of digital platforms in the literacy process of schools in the state of são paulo: challenges to teacher training and pedagogical autonomy
Keywords: Plataformas digitais; Trabalho docente; Políticas públicas educacionais; Educação digital; Pandemia; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade